Vloga medialnega patelofemoralnega ligamenta pri stabilizaciji pogačice v patelofemoralnem sklepu in načini rekonstrukcije patelofemoralnega ligamenta - Goslar, Tomaž (Medicinski razgledi, 2007)
Patello-femoral instability is a common clinical problem. It is most often seen with youngsters, females and professional athletes. Medial patello-femoral ligament (MPFL) has been found to be most important static, soft-tissue stabilizer of patella, preventing patellar shifts outward and therefore its dislocation and subluxation. According to studies, increased patellar mobility is encountered in knees with positive anamnesis of patellar dislocation and is a consequence of medial retinacular laxity. In order to correct the excessive patellar mobility a reconstruction of MPFL as a primary medio-lateral patellar stabilizer is necessary. More then 100 procedures have been described for the treatment of patellar instability, but the majority focuses on dynamic patellar stabilizers. To gain back patellar stability a repair or reconstruction of MPFL is necessary. However, none of the described techniques has been adopted as a golden standard so far.
Keywords: Knee Injuries; Tetiva, prenos; Pogačica, ligament; Patella; Koleno, poškodbe; Injuries; Patellar Ligament; Pogačica; Sklep, nestabilni; Surgery; Joint Instability; koleno; Tendon Transfer; poškodbe; ligamenti; kirurško zdravljenje